The influence of the brazilian mathematical olympic of public schools on the basic education development index: An analysis in the municipality of Coruripe-Alagoas - Lima, Elielson Magalhães; Silva, Jailson José da; Rodrigues, Vagno Izidorio; Nascimento, César de Oliveira; Júnior, Jalon Saturnino de Oliveira (Seven Editora, 2023)
This article aims to analyze the influence of the Brazilian Mathematical Olympiad of Public and Private Schools (OBMEP) on the Basic Education Indexes (IDEB) in a municipality in Alagoas from 2007 to 2017. It was developed from the collection and analysis of data through interviews and semi-structured questionnaires prepared by the proponents themselves, and directed to the coordinators of the referred municipality, in order to analyze the influence of the Brazilian Mathematical Olympiad of Public Schools on the results of the IDEB. From the calculation of the data obtained, it was clear that since the insertion of programs aimed at improving the performance of students in the OBMEP was also reflected, also reflected improvements in the results of the IDEB of the municipality, which reached 6.3 points in 2017, which means an increase of 1.9 points compared to 2015. DOI:https://doi.org/10.56238/devopinterscie-189